Whither State Sector Enterprises in Kerala? - P Mohanan Pillai (Economic and Political Weekly February 17-24,1990, 1990)
This paper summarises the major findings of a larger study on the performance of state sector manufacturing enterprises in Kerala. Why has the financial performance of state sector enterprises been so poor? To answer this question, the capital structure of these enterprises and its implications for their financial viability have been examined. The physical performance of the units on a sample basis has been evaluated and the major problems they confront on the technology front have been briefly discussed. Also examined are the factors responsible for the growing 'sickness' among state sector enterprises